The effect of perceived trust, perceived security and attitude on online purchase intention in Malaysia public universities - Meskaran, Fatemeh (2015)
The popularity of online shopping in electronic commerce (e-commerce) is significantly tempered with concerns over perceived trust and perceived security in online purchasing. Lack of trust and security issue cause the online users to avoid participating in online purchasing and instead they use the online environment more for non-shopping activities more. Despite the increased awareness of trust and security issues, their antecedents in online purchase intentions have not been adequately examined. This study proposes a conceptual model to evaluate the effects of perceived trust, perceived security, attitude and their antecedents on online purchase intention. A quantitative methodology is used, and questionnaires were sent to students in six public universities in the Klang Valley of Malaysia. A total of 438 Malaysian students participated in this online survey. Structural Equation Modeling was used to evaluate the proposed model. The findings show that attitude, perceived trust and perceived security have a significant direct effect on online purchase intention. Customers’ attitude towards online purchasing is the most important factor in predicting online purchase intention. On the other hand, when the website is perceived as secure and trustworthy the intention to do online purchasing will increase. In addition, factors such as reputation, information quality, third party endorsement and familiarity are found to be the antecedents of perceived trust while factors such as controllability, reputation and familiarity are exhibited as antecedents of perceived security. Moreover, perceived ease of use and perceived security are two antecedents of attitude. Attitude mediates the effect of perceived security on online purchase intention partially. Hence, this study concludes that online vendors and online shop managers should give particular attention to online customers’ attitude towards online purchasing, their perception of trust, security and their antecedents, for having more potential online customers and increasing intention to do online purchasing.